La inclusión educativa técnico superior de personas con discapacidad cognitiva desde la percepción de estudiantes regulares - Hermoza Puente Arnao, Anite (2021)
The present study is characterized as a qualitative and descriptive research. It was developed under a phenomenological design involving the superior educational inclusion of people with cognitive disabilities, focusing on the perception of students without cognitive disabilities. To obtain information for this study, twelve semi-structured interviews were carried out. The participants for the interviews were between the ages of eighteen and twenty-seven, and all formed part of a superior technical institution. The interviews were transcribed and analyzed in order to categorize the information provided. The categories that were used to analyze the data were the following: perception about people with cognitive disabilities, perception towards other agents of the inclusion process, interaction between students with cognitive disabilities and students without cognitive disabilities and lastly their perception about educational inclusion. The criteria of rigor used were judgment of expert and content analysis, which allowed the contrast of different perspectives for the data collected. The results revealed that participants modify their attitudes and perceptions about people with disabilities after sharing a semester of study with students in an educational inclusion program. This conclusion is evidenced by the continuous interaction during academic activities, the friendly relationships displayed and the behaviors demonstrating support towards students with disabilities. The participants reveled that the educational inclusion generates changes at different levels. At a personal level, the participants shared that they accepted the responsibility to support their peers with intellectually disabilities to academically succeed. During the process, the participants learned and developed skills and strategies to help their other peers in terms of organization, comprehension and internalization of the content.